Impact of new hypertension guidelines on target organ damage screening in a Shanghai community‐dwelling population. Issue 10 (18th September 2019) - Wang, Qian; Chao, Huijuan; Zheng, Shuping; Tan, Isabella; Butlin, Mark; Avolio, Alberto; Zuo, Junli
Abstract: Recently, the 2017 ACC/AHA released new hypertension guidelines and proposed a redefinition of hypertension from 140/90 to 130/80 mm Hg. This study assesses the impact of the lower threshold for hypertension diagnosis on the association of hypertension with target organ damage (TOD). Health checks were conducted in a community‐dwelling population in Shanghai in 2017 (N = 10 826; 43.26% mean, age 62 ± 12 years [range 29‐95 years]). Subclinical TOD indices were quantified in terms of left ventricular hypertrophy (LVH) by electrocardiogram (Sokolow‐Lyon standard), estimated glomerular filtration rate (eGFR), and presence of proteinuria. Information on clinical TOD was obtained by questionnaire. Arteriosclerotic cardiovascular disease (ASCVD) was determined by the 2013 ACC/ AHA recommended guidelines. Compared to the higher threshold (140/90 mm Hg), the lower threshold (130/80 mm Hg) was associated with variable rates of increased detection of hypertension and TOD: (a) Hypertension: incidence of hypertension, 29.5% (51.8%‐81.5%) increase in persons with hypertension if the threshold of 130/80 mm Hg is used; (b) Subclinical TOD: LVH, 20.8%; eGFR (30‐60 mL/min per 1.73 m 2 ), 23.7%; proteinuria, 23.5%; (c) Clinical TOD: chronic kidney disease (CKD) IV (eGFR＜30 mL/min per 1.73 m 2 ), 3.1%; diabetes (fasting glucose ≥7.0 mmol/L or HbA1C＞7.0%), 24.3%; stroke, 26.4%; chronic heart disease, 28.1%; acute myocardial infarction, 19.5% (69.4% to 88.9% of total of 36); ASCVD ≥10%, 29.3%. The lower threshold was associated with a significantly higher detection rate of clinical and subclinical TOD of approximately 20% compared to the higher threshold. 15%‐20% of TOD and 29% of ASCVD were also found below the lower threshold of hypertension.